2023
DOI: 10.1097/phm.0000000000002195
|View full text |Cite
|
Sign up to set email alerts
|

The PRINCOVID Retrospective Study

Abstract: Objective The aim of the study is to characterize pressure injuries, identify risk factors, and develop a predictive model for pressure injuries at intensive care unit admission for critical COVID-19 patients. Design This study was a retrospective analysis of a consecutive sample of patients admitted to intensive care unit between May 2020 and September 2021. Inclusion criteria encompassed the diagnosis of acute respiratory distress syndrome due to SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In the subgroup analysis of patient source, the meta‐analysis results indicated no significant association between hypertension and PU in Asia group (OR = 1.12, 95% CI = 0.83–1.50, I 2 = 63%, p = 0.46) 11 , 12 , 17 , 20 , 22 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 and Non‐Asia group (OR = 1.20, 95% CI = 0.75–1.94, I 2 = 88%, p = 0.45). 10 , 18 , 19 , 21 , 23 , 26 In the subgroup analysis of study design, the results also showed no significant association between hypertension and PU in cohort study (OR = 1.16, 95% CI = 0.84–1.61, I 2 = 63%, p = 0.36) 10 , 11 , 17 , 21 , 22 , 27 , 28 , 31 , 32 and case–control study (OR = 1.14, 95% CI = 0.79–1.64, I 2 = 82%, p = 0.49). 12 , 18 , 19 , 20 , 23 , 24 , 25 , 26 , 29 , 30 Due to the primary disease difference, subgroup analysis was performed based on primary disease, and the results showed that there was a significant association between hypertension and PU in COVID‐19 patients(OR = 1.73, 95% CI = 1.35–2.22, I 2 = 0%, p < 0.0001), 10 , 21 , 26 whereas no association was found in str...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subgroup analysis of patient source, the meta‐analysis results indicated no significant association between hypertension and PU in Asia group (OR = 1.12, 95% CI = 0.83–1.50, I 2 = 63%, p = 0.46) 11 , 12 , 17 , 20 , 22 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 and Non‐Asia group (OR = 1.20, 95% CI = 0.75–1.94, I 2 = 88%, p = 0.45). 10 , 18 , 19 , 21 , 23 , 26 In the subgroup analysis of study design, the results also showed no significant association between hypertension and PU in cohort study (OR = 1.16, 95% CI = 0.84–1.61, I 2 = 63%, p = 0.36) 10 , 11 , 17 , 21 , 22 , 27 , 28 , 31 , 32 and case–control study (OR = 1.14, 95% CI = 0.79–1.64, I 2 = 82%, p = 0.49). 12 , 18 , 19 , 20 , 23 , 24 , 25 , 26 , 29 , 30 Due to the primary disease difference, subgroup analysis was performed based on primary disease, and the results showed that there was a significant association between hypertension and PU in COVID‐19 patients(OR = 1.73, 95% CI = 1.35–2.22, I 2 = 0%, p < 0.0001), 10 , 21 , 26 whereas no association was found in str...…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 18 , 19 , 21 , 23 , 26 In the subgroup analysis of study design, the results also showed no significant association between hypertension and PU in cohort study (OR = 1.16, 95% CI = 0.84–1.61, I 2 = 63%, p = 0.36) 10 , 11 , 17 , 21 , 22 , 27 , 28 , 31 , 32 and case–control study (OR = 1.14, 95% CI = 0.79–1.64, I 2 = 82%, p = 0.49). 12 , 18 , 19 , 20 , 23 , 24 , 25 , 26 , 29 , 30 Due to the primary disease difference, subgroup analysis was performed based on primary disease, and the results showed that there was a significant association between hypertension and PU in COVID‐19 patients(OR = 1.73, 95% CI = 1.35–2.22, I 2 = 0%, p < 0.0001), 10 , 21 , 26 whereas no association was found in stroke patients(OR = 0.80, 95% CI = 0.29–2.18, I 2 = 72%, p = 0.66), 24 , 30 geriatric disease (OR = 1.32, 95% CI = 0.78–2.24, I 2 = 0%, p = 0.30), 20 , 23 , 28 ICU patients(OR = 0.89, 95% CI = 0.56–1.42, I 2 = 61%, p = 0.62) 17 , 22 , 31 , 32 and surgical patients (OR = 1.10, 95% CI = 0.70–1.73, I 2 = 82%, p = 0.68). 11 , 12 , 18 , …”
Section: Resultsmentioning
confidence: 99%
“…In a study of critically ill COVID patients, the face was commonly affected by LPP and these lesions were related to the use of external devices (such as feeding devices, high-flow endotracheal tubes and standard nasal cannula) and positioning in the prone position (Teixeira-Vaz et al, 2023). According to systematic reviews of oral manifestations in COVID patients, ulcerative lesions, including those of traumatic origin, have been found (Gupta et al, 2023;Kot et al, 2023), but without a specific diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, It is essential to emphasize the importance of quality ICU care for patients with comorbidities in order to prevent the occurrence of PPL, including in the oral cavity. In a study evaluating a predictive model for PPL in critically ill COVID patients, arterial hypertension was a potential factor associated with these lesions (Teixeira-Vaz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation